2020
DOI: 10.1002/jor.24781
|View full text |Cite
|
Sign up to set email alerts
|

Increased volume and collagen crosslinks drive soft tissue contribution to post‐traumatic elbow contracture in an animal model

Abstract: Post‐traumatic joint contracture (PTJC) in the elbow is a biological problem with functional consequences. Restoring elbow motion after injury is a complex challenge because contracture is a multi‐tissue pathology. We previously developed an animal model of elbow PTJC using Long‐Evans rats and showed that the capsule and ligaments/cartilage were the primary soft tissues that caused persistent joint motion loss. The objective of this study was to evaluate tissue‐specific changes within the anterior capsule and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…Similarly, the ratio between such crosslinks and those typical of soft connective tissues was upregulated in idiopathic pulmonary fibrosis, as were the density of mature crosslinks and the tissue stiffness, but not the collagen content [85]. Further supporting our modeling approach, the mature/immature crosslink ratio correlated positively with changes in the mechanical stiffness of lateral collateral ligament following injury [72], suggesting a dominant role of tissue ‘quality’ over its ‘quantity’ towards determining tissue fibrosis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, the ratio between such crosslinks and those typical of soft connective tissues was upregulated in idiopathic pulmonary fibrosis, as were the density of mature crosslinks and the tissue stiffness, but not the collagen content [85]. Further supporting our modeling approach, the mature/immature crosslink ratio correlated positively with changes in the mechanical stiffness of lateral collateral ligament following injury [72], suggesting a dominant role of tissue ‘quality’ over its ‘quantity’ towards determining tissue fibrosis.…”
Section: Discussionmentioning
confidence: 80%
“…Based on the inadequacy of a proportional link between k 1 and ϕ c , we hypothesize that this constitutive relation should additionally account for the progressive maturation of the newly-formed collagen network. Indeed, alterations in the degree and type of crosslinking have been reported to affect the emergent mechanical behavior of soft tissues such as tendons [72], uterine cervix [73], and skin wounds [10]. For simplicity, we focus on the degree of network crosslinking and consider a nonlinear relation between k 1 and ϕ c , mediated by a crosslinking agent, ξ c : where a ≥ 1 is a phenomenological exponent controlling the degree of tissue nonlinearity associated with a given crosslinking.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work in the same rat elbow model found that the LCL was a significant contributor to contracture at late time points; the increase in BV or TV of the EC object due to injury could be a factor. 11,12 Focusing on the largest EC object in each limb, injury, but not sex, was a significant factor for BV, TV and BV/TV (Figure 6B-D). The increase in TV and relatively small increase in BV that occurred with limb injury and immobilization showed that the larger EC objects were structurally less dense compared to similar (smaller) objects in control and contralateral limbs (Figure 6B-D).…”
Section: Discussionmentioning
confidence: 96%
“…to contracture have also been evaluated. [10][11][12] However, these previous studies that investigated disease etiology, progression and recovery were conducted only with male animals; it remains unknown whether female animals would exhibit similar responses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aimed to evaluate the effects of SV and LS in two established preclinical models of contracture. Two SV and LS dosing strategies were tested in an elbow-specific rat injury model in vivo , which normally causes loss of elbow function, capsule fibrosis, and mild arthritis ( Lake et al, 2016 ; Dunham et al, 2017a ; Dunham et al, 2017b ; Dunham et al, 2018a ; Dunham et al, 2018b ; Dunham et al, 2019 ; Dunham et al, 2020 ; Dunham et al, 2021 ; Reiter et al, 2019 ; Reiter et al, 2021a ; Reiter et al, 2021b ) . The in vivo model provides translatability of SV and LS therapy and joint-wide impact on multiple soft tissues (i.e., capsule and cartilage).…”
Section: Introductionmentioning
confidence: 99%